ANALYSIS OF NURSING CARE IN PATIENTS WITH SENSORY PERCEPTION DISORDERS THROUGH APPLICATION OF THERAPY THOUGHT STOPPING - afaninda dwi khairini; Angga Sugiarto; Suyanta Suyanta (INTERNATIONAL JOURNAL OF NURSING AND MIDWIFERY SCIENCE (IJNMS), 2023)
Schizophrenia is a serious mental disorder that can affect individual thoughts, feelings and behavior. Schizophrenia is part of a psychotic disorder which is primarily characterized by loss of understanding of reality and loss of self-view. Thought stopping is one of a cognitive behavioral psychotherapy technique that can be used to help clients change their thought processes. Sources of data obtained using primary and secondary data, primary data obtained by means of interviews with respondents, while secondary data related to case studies obtained from medical records.The subjects of this case study were schizophrenic patients with sensory perception disorders at Prof Dr Soerojo Psychiatric Hospital, with the number of case study subjects 3 patients who experience sensory perception disorders. The instrument is a measuring tool to measure what will be measured. The instrument for this case study method uses the PYSRAT (Psychotic Symptom Rating Scale). The nursing actions applied to three schizophrenic clients with sensory perception disorders in this case study focused on the application of thought stopping. The intervention was carried out 3 times with a duration of 10-15 minutes at each visit. Based on the application that has been done on clients, it is known that thought stopping can help reduce signs and symptoms and control sensory perceptual disorders. The results of sensory perception getting better. .